Phosphopantetheine Adenylyltransferase from Escherichia coli: Investigation of the Kinetic Mechanism and Role in Regulation of Coenzyme A Biosynthesis - Miller, J. Richard (American Society for Microbiology (ASM), 2007)
Phosphopantetheine adenylyltransferase (PPAT) from Escherichia coli is an essential hexameric enzyme that catalyzes the penultimate step in coenzyme A (CoA) biosynthesis and is a target for antibacterial drug discovery. The enzyme utilizes Mg-ATP and phosphopantetheine (PhP) to generate dephospho-CoA (dPCoA) and pyrophosphate. When overexpressed in E. coli, PPAT copurifies with tightly bound CoA, suggesting a feedback inhibitory role for this cofactor. Using an enzyme-coupled assay for the forward-direction reaction (dPCoA-generating) and isothermal titration calorimetry, we investigated the steady-state kinetics and ligand binding properties of PPAT. All substrates and products bind the free enzyme, and product inhibition studies are consistent with a random bi-bi kinetic mechanism. CoA inhibits PPAT and is competitive with ATP, PhP, and dPCoA. Previously published structures of PPAT crystallized at pH 5.0 show half-the-sites reactivity for PhP and dPCoA and full occupancy by ATP and CoA. Ligand-binding studies at pH 8.0 show that ATP, PhP, dPCoA, and CoA occupy all six monomers of the PPAT hexamer, although CoA exhibits two thermodynamically distinct binding modes. These results suggest that the half-the-sites reactivity observed in PPAT crystal structures may be pH dependent. In light of previous studies on the regulation of CoA biosynthesis, the PPAT kinetic and ligand binding data suggest that intracellular PhP concentrations modulate the distribution of PPAT monomers between high- and low-affinity CoA binding modes. This model is consistent with PPAT serving as a “backup” regulator of pathway flux relative to pantothenate kinase.